2012
DOI: 10.1210/jc.2012-1872
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging Analysis of Food-Related Brain Activity in Patients with Lipodystrophy Undergoing Leptin Replacement Therapy

Abstract: This study demonstrated the insufficiency of postprandial suppression of food-related neural activity and formation of satiety feeling in lipodystrophic patients, which was effectively restored by leptin. The findings in this study emphasize the important pathological role of leptin in eating disorders in lipodystrophy and provide a clue to understanding the action mechanism of leptin in human, which may lead to development of novel strategies for prevention and treatment of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…1 has been published so far in metreleptin treatment-naive subjects with leptin-deficiency. Furthermore, the current study is the first to describe metreleptin treatment-associated alterations in resting state connectivity compared with published fMRI studies with eventrelated designs ranging from n = 1 to 3 subjects (33)(34)(35)(36); one study reported on 10 subjects who were not treatment naive (13). A replication of the current fMRI results in larger samples would be valuable.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…1 has been published so far in metreleptin treatment-naive subjects with leptin-deficiency. Furthermore, the current study is the first to describe metreleptin treatment-associated alterations in resting state connectivity compared with published fMRI studies with eventrelated designs ranging from n = 1 to 3 subjects (33)(34)(35)(36); one study reported on 10 subjects who were not treatment naive (13). A replication of the current fMRI results in larger samples would be valuable.…”
Section: Discussionmentioning
confidence: 74%
“…These findings also suggest an influence of leptin on the other component contributing to the formation of human eating behavior, that is, hedonic eating, which is the drive to eat for pleasure in the absence of an energy deficit (12). Human behavioral data support the hypothesis that leptin affects both components of eating control (4,13).…”
mentioning
confidence: 61%
“…However, dual X-ray absorptiometry analysis failed to reveal a significant increase in fat mass upon rosiglitazone treatment, likely due to a lack of sensitivity of the method. This raises the question of the presence of remaining fat pads in BSCL patients, although the presence of WAT in BSCL2 patients has been detected by different techniques (dual energy X-ray densitometry or magnetic resonance imaging) [31,32]. Actually, recombinant leptin injection is the gold-standard therapy in adults [33,34] and children [35] with BSCL.…”
Section: Discussionmentioning
confidence: 99%
“…Using functional MRI, Aotani et al [41] have recently shown that leptin therapy helps to suppress postprandial neuronal activity in certain brain areas, which can lead to improved satiety. All this clearly suggests that leptin has a strong influence on the central regulation of feeding, and this might be an important contributor to its metabolic effects.…”
Section: Mechanisms Of Leptin Actionmentioning
confidence: 99%